2008
DOI: 10.1021/ja8043085
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Electron Transfer Activity From Single CdSe/ZnS Quantum Dots

Abstract: Electron transfer activity from excited single CdSe/ZnS core/shell quantum dots (QDs) to adsorbed Fluorescein 27 was studied by single QD fluorescence spectroscopy. In comparison with QDs, the QD-acceptor complexes showed a shorter average and broader distribution of QD emission lifetimes due to electron transfer to adsorbates. Large fluctuation of lifetimes in single QD/dye complexes was observed, indicating intermittent electron transfer activity from QDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
107
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(123 citation statements)
references
References 17 publications
15
107
0
Order By: Relevance
“…The size-dependent differences in av upon addition of quencher as shown in Figure 1a and b are a direct result of CT-style PL quenching. It is known from different semiconductor nanocrystal CT studies, that PL lifetimes decrease with increasing CT acceptors adsorbed to the surface [38,39]. For larger NCs av changes to much smaller degree (another indicator that I 2 is adsorbed to the NC surface), while the smaller NC sample shows a decrease in av that surpasses the decrease in PL.…”
Section: Resultsmentioning
confidence: 99%
“…The size-dependent differences in av upon addition of quencher as shown in Figure 1a and b are a direct result of CT-style PL quenching. It is known from different semiconductor nanocrystal CT studies, that PL lifetimes decrease with increasing CT acceptors adsorbed to the surface [38,39]. For larger NCs av changes to much smaller degree (another indicator that I 2 is adsorbed to the NC surface), while the smaller NC sample shows a decrease in av that surpasses the decrease in PL.…”
Section: Resultsmentioning
confidence: 99%
“…This notion has been suggested in previous reports of intermittent ET dynamics in single QD-molecular acceptor complexes. 61,62 A recent computational study showed that the presence of charge affects the energy and wave function of excitons in QDs. 73 Spectral diffusion of up to 50 meV for single CdSe/ ZnS QDs has also been observed.…”
mentioning
confidence: 99%
“…That is, high intensity levels are characterized by long lifetime values and low intensity levels by short lifetime values, consistent with previous reports. 10,11 Fluctuations in the fluorescence intensity and lifetime of individual quantum dots have been attributed to the variation of trapped charges in and around the QDs and the resulting Auger relaxation processes. For QD625-16AT-C 60 and QD625-6AT-C 60 , the fluctuating fluorescence lifetime and intensity may result from both the Auger relaxation and photo-induced electron transfer processes.…”
Section: Resultsmentioning
confidence: 99%